Analyze the Application of Blockchain Technology in Digital Forensics and Hunt for Threats Lurking in Security - Muhamad Irfan Florid; Hendratna Mutaqin; Pupung Purnamasari (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Many institutions, including law enforcement agencies and regulatory authorities, are investing in the creation of tools and knowledge in the rapidly growing field of blockchain forensics. Effective blockchain forensics will likely become more important in fighting financial crime as the use of blockchain technology continues to grow. Information security aspects are key in digital forensics, especially in protecting digital evidence from potential threats or manipulation during the investigation process. various sources (Internet, google scholar, sage, elsevier)In general, IoTCF improves existing digital forensics in three aspects: reducing examination costs and resources, establishing connections with third parties, and increasing the profitability of the process.origin process integrates group signature methods blockchain and cryptography to offer proof of existence and privacy protection of records. The critical processes of the origin process are the submission list, recipient, sender, origin auditor, and certificate authority. Deep learning model for Ethereum in threat hunting and testing the performance of the model, where the performance evolution in terms of accuracy is 97.72% in attack detection while classification attacks were at 99.4%. Ethereum cryptocurrency security requires proper security to minimize vulnerabilities and risks.Conclusion The application of blockchain technology has significantly improved digital forensics Existing vulnerability detection programs have faulty detection mechanisms. Traditional techniques that have been relied upon for decades have shown high rates of false positives and negatives, making them unreliable.